Assessment of Soluble Intercellular Adhesion Molecule-1 Based Rapid Test for a Quick Diagnosis of Atypical Prelabor Rupture of Membranes in the Emergency Setting - Lin Tang; Zhongyi Zhu; Xinghui Liu; Yayi Hu (IMR Press, 2023)
Background: There is an urgent need to evaluate the clinical value of soluble intercellular adhesion molecule-1 (sICAM-1) based rapid tests (Leakection) for a quick and relatively accurate diagnosis of prelabor rupture of membranes (PROM), especially atypical PROM, in the emergency setting. This is a retrospective study. The data collection was planned after all the index test and reference standard were performed retrospectively. Methods: A total of 267 pregnant women complaining of increased vaginal effusion were recruited. For preliminary diagnoses, patients were examined by observing posterior vault pooling and by performing nitrazine tests and Leakection tests. PROM was subsequently confirmed with a clinical diagnosis consisting of both patient history and the results of a panel of tests. The sensitivity and specificity of posterior vault pooling, Leakection from the posterior vault and the nitrazine test in the emergency setting were retrospectively reported to evaluate their power of diagnosis in PROM. Results: One hundred thirty-two patients were diagnosed with PROM, and 135 patients were found not to have PROM. When samples were collected from the posterior vault, Leakection had a sensitivity of 97.0%, a specificity of 91.1%, and a false negative rate of 3.0%. In contrast, the nitrazine test had a sensitivity of 68.9%, a specificity of 100.0%, and a false negative rate of 31.1%. Conclusions: Leakection is a noninvasive and inexpensive rapid test for the screening and diagnosis of PROM with both high sensitivity and specificity. This test can greatly aid in the clinical diagnosis of PROM, especially atypical PROM, in the emergency setting.